2012
DOI: 10.3390/molecules17010688
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of β-Carotene Supplementation on the Pharmacokinetics of Nelfinavir and Its Active Metabolite M8 in HIV-1-infected Patients

Abstract: β-Carotene supplements are often taken by individuals living with HIV-1. Contradictory results from in vitro studies suggest that β-carotene may inhibit or induce cytochrome P450 enzymes and transporters. The study objective was to investigate the effect of β-carotene on the steady-state pharmacokinetics of nelfinavir and its active metabolite M8 in HIV-1 infected individuals. Twelve hour nelfinavir pharmacokinetic analysis was conducted at baseline and after 28 days of β-carotene supplementation (25,000 IU tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 37 publications
(46 reference statements)
0
9
0
Order By: Relevance
“…The role of micronutrient supplementation in stabilizing or delaying immune decline in persons not on ART can only be evaluated within a controlled clinical trial. A pharmaceutical grade formulation of the high-dose micronutrients was chosen for the experimental intervention in this clinical trial because of its bioavailability and stability, which has been problematic in other settings [16,29]. While demanding of participants, the 16-capsule daily regimen allows for a more definitive trial given pharmaceutical stability and adherence.…”
Section: Discussionmentioning
confidence: 99%
“…The role of micronutrient supplementation in stabilizing or delaying immune decline in persons not on ART can only be evaluated within a controlled clinical trial. A pharmaceutical grade formulation of the high-dose micronutrients was chosen for the experimental intervention in this clinical trial because of its bioavailability and stability, which has been problematic in other settings [16,29]. While demanding of participants, the 16-capsule daily regimen allows for a more definitive trial given pharmaceutical stability and adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Several properties of this micronutrient supported the hypothesis that it could influence HIV disease, including its importance in maintaining normal immune responses, its ability to act as an antioxidant, and its role as a provitamin A molecule. There are few clinical trials investigating the effect of beta-carotene supplementation (11,12) in HIV/AIDS patients. The studies do not show a benefit, but they involved a relatively small sample size.…”
mentioning
confidence: 99%
“…While nine studies investigated the effects of food or nutrient supplement on ARV pharmacokinetics [ 12 , 14 , 25 , 27 , 32 , 38 , 42 , 43 , 44 ]. The rest of the studies explored the pharmacokinetic interactions between ARV and vitamins or minerals [ 15 , 29 , 34 , 36 , 37 , 40 ], and dietary supplements [ 28 , 31 , 33 , 35 , 39 , 41 ]. Most studies showed non-significant changes in ARV pharmacokinetic parameters when co-administered with meals.…”
Section: Resultsmentioning
confidence: 99%